2023
DOI: 10.3390/nu15071723
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk between Gut Microbiota and White Adipose Tissue Mitochondria in Obesity

Abstract: Adipose tissue (AT) dysregulation is a key process in the pathophysiology of obesity and its cardiometabolic complications, but even if a growing body of evidence has been collected over recent decades, the underlying molecular basis of adiposopathy remains to be fully understood. In this context, mitochondria, the intracellular organelles that orchestrate energy production and undergo highly dynamic adaptive changes in response to changing environments, have emerged as crucial regulators of both white (WAT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 149 publications
0
9
0
Order By: Relevance
“…Obesity-associated microbiota influences the efficiency of calorie uptake from ingested foods, host energy harvesting, insulin resistance, hepatic metabolism, inflammation, as well as central regulation of appetite and satiety and food reward signalling, which all have crucial roles in obesity. Moreover, some strains of bacteria and their metabolic products might directly target the brain by vagal afferent innervation or immune-neuroendocrine mechanisms (36,37).…”
Section: Obesity: Nods Of Epidemiology and Etiopathogenesismentioning
confidence: 99%
“…Obesity-associated microbiota influences the efficiency of calorie uptake from ingested foods, host energy harvesting, insulin resistance, hepatic metabolism, inflammation, as well as central regulation of appetite and satiety and food reward signalling, which all have crucial roles in obesity. Moreover, some strains of bacteria and their metabolic products might directly target the brain by vagal afferent innervation or immune-neuroendocrine mechanisms (36,37).…”
Section: Obesity: Nods Of Epidemiology and Etiopathogenesismentioning
confidence: 99%
“…In the review by Rinninella et al, a complete taxonomic gut microbiota composition is reported, with an exhaustive description of the genera of the above-mentioned classes [12]. Along the GI tract, there is a great variability of microbiota concentration, with a low presence in the upper intestine (10-10 3 cells/g) and a great abundance in the colon (10 11 -10 12 cells/g), representing about 0.2 kg of weight in a healthy adult man of 70 kg [15].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In May 2022, the World Health Organization published a report on the status of the obesity pandemic in Europe, which revealed that approximately 60% of individuals residing in the region are either overweight or obese [ 2 ]. Obesity can result in metabolic dysregulation, which can interfere with the proper functioning of key metabolic organs, including the liver, adipose tissue, pancreas, muscles, and intestines [ 3 4 5 ]. Studies on the distribution and determinants of diseases in populations have shown that there is a connection between high body mass index (BMI) and various chronic conditions such as non-alcoholic fatty liver disease (NAFLD) [ 6 ], cardiovascular disease [ 7 8 ], diabetes [ 7 9 ], multiple cancers [ 10 11 12 ], musculoskeletal diseases [ 13 14 ], and chronic kidney disease [ 7 ].…”
Section: Metabolic Diseasesmentioning
confidence: 99%